Sistem Informasi Pengajuan Topik dan Dosen Pembimbing Tugas Akhir Berbasis Website Dengan Framework Laravel (Studi Kasus: Fakultas Ilmu Komputer Universitas Pembangunan Nasional Veteran Jakarta) - Septriediana Amalia Putrie (2024)
Universitas Pembangunan Nasional Veteran Jakarta is a state university which has seven faculties, one of which is the Faculty of Computer Science. Currently, the guidance registration process for submitting topics and thesis/final assignment supervisors at the Faculty of Computer Science is still done manually using Google forms and spreadsheets. This is considered ineffective because the data processing process is still focused on human resources which allows human errors to occur, such as incorrect data input, unsafe data storage, and data redundancy. This research aims to build a website-based information system for submitting topics and final assignment supervisors by automating quotas for each topic and lecturer. This system was developed using the waterfall model, the Laravel framework for the PHP programming language, and MySQL as a database management system. The main functions of the system include submitting academic recommendations, submitting topics, submitting supervisors, as well as processing data on topics and supervisors. The result of this research is the implementation of a website which is expected to simplify and increase the efficiency of the thesis/final project guidance registration process for all related parties, including students, lecturers, study program heads, and study program staff.